Sistem Informasi Pengolahan Data Status Gizi Balita Berbasis Web (Studi Kasus: UPTD Puskesmas Miri, Kecamatan Miri, Kabupaten Sragen) - Adella Intan Pramesthi; S.M. Santi Winarsih; Omega Rimba Gemilang (Universitas Boyolali, 2021)
Nutritional status is a measure of success in fulfilling nutrition for children as indicated by the child's weight and height. The UPTD Puskesmas Miri has 56 posyandu and has limitations in manual recording. The Information System for Toddler Nutritional Status Data Processing is an application that makes it easy for midwives to process posyandu data and the system will process the data into Toddler Nutritional Status for reports to a nutritionist to find out the nutritional development of toddlers every month.This system is built using the PHP programming language with a MySQL database for data storage. The result of this system is that it can process information related to posyandu, such as: toddler data, immunization data and weighing data. In making this Information System, it is hoped that it can help the performance and make it easier for midwives and nutritionists in terms of processing data on nutritional status of toddlers